Low Cost Training Models for Videothoracoscopic Surgical Training - (:unkn) unknown (BENTHAM SCIENCE PUBL LTD, 2021)
Objective: We designed novel practical simulation models for VATS lung nodule palpation and vessel dissection, and subsequently evaluated the performances of the residents in our thoracic surgery program to account for the appropriate level of difficulty and grade the learning experience. Methods: Artificial lung nodules were formed by injecting sheep heart lung blocks with either cyanoacrylate or construction grade silicone diluted with synthetic thinner. Artificial lung and vessel environment was formed using a sponge, with a tube balloon placed inside a tunnel within the sponge and fixed with a flexible glue. Both models were placed in a standard laparoscopy training box, and both conventional and minimally invasive surgery instruments were used as applicable per the attendee's discretion. Results: In the lung nodule simulation, among 4 residents (postgraduate year (PGY) 1, 3, 4 and 4), the average time to palpating the first nodule was 57 seconds,and the average time of whole lung palpation was 7,7 minutes. In the vascular dissection model, of the five residents (PGY 4, 3, 3, 3, 1), median distance dissected at the first attempt was 3,1 cm (1-4,7), and it was shorter in the second attempt, 2,5 cm (2-3,2). Median dissection duration was shorter in the second attempt (5 vs. 3 minutes). All residents were able to complete the dissection of the balloon from the sponge within 9 attempts. Conclusion: Surgical simulation models can be created with minimal resources, allowing for enough difficulty to maintain engagement and accomplish progressive skill through practice. As clinics shift case volume to minimally invasive procedures, resident exposure to open cases can become more scarce; so simulation training in thoracic surgery can not be perceived as a luxury, it has to be accessible even though the learning environment does not have resources to invest in virtual reality sets or computerized simulators.
Keywords: Medical education; surgical simulation; videothoracoscopy; lung nodule simulation; anatomical models; laparos-copic equipment; EDUCATION; LOBECTOMY; SURGERY